Tindak Pidana Pemberontakan dalam Perspektif Hadits - Hurun Sajidah Almumtazah; Tajul Arifin (Universitas Muhammadiyah Yogyakarta, 2023)
Rebellion is a crime that is strictly prohibited in Islam. This article aims to explore the Hadith perspective on the issue of rebellion. Hadith is a collection of sayings and actions of Prophet Muhammad (PBUH), considered as one of the main sources of Islamic law. The article begins by defining the concept of rebellion and its various forms. It then highlights the importance of obeying legitimate authority and presents views according to Islamic law and positive law in Indonesia, as well as the consequences of rebelling against them.The article also discusses Hadith that emphasizes the importance of unity among Muslims and the dangers of division and rebellion. In addition, the article discusses the consequences of rebellion, which not only disrupt peace and societal stability but also go against the principles of justice and fairness. The article also emphasizes the importance of peaceful protest and legitimate means to seek change, rather than resorting to rebellion and violence.Overall, Hadith emphasizes the importance of upholding the law and avoiding rebellion, which can cause chaos and instability. Muslims are urged to maintain unity and work towards peaceful means in solving problems and bringing positive change in society. The article concludes that obedience to Hadith can be a powerful tool in promoting peace, justice, and harmony in society.Keyword: perspective of Hadits, crime, rebellion, positive law and Islamic Law AbstrakPemberontakan merupakan tindak pidana yang dilarang secara tegas dalam Islam. Penelitian berupa tulisan ini bertujuan untuk menjelajahi perspektif Hadist mengenai isu pemberontakan. Hadist adalah kumpulan ucapan dan tindakan Nabi Muhammad (S.A.W), yang dianggap sebagai salah satu sumber utama hukum Islam.Tulisan ini dimulai dengan mendefinisikan konsep pemberontakan dan berbagai bentuknya. Kemudian menyoroti pentingnya patuh pada otoritas yang sah dan juga memaparkan pandangan menurut hukum islam dan hukum positif yang ada diindonesia serta konsekuensi dari memberontak terhadap mereka. Tulisan ini juga membahas Hadist yang menekankan pentingnya persatuan umat Islam dan bahaya dari perpecahan dan pemberontakan.Selain itu, tulisan ini membahas konsekuensi pemberontakan, yang tidak hanya mengganggu perdamaian dan stabilitas masyarakat tetapi juga bertentangan dengan prinsip keadilan dan keadilan. Tulisan ini juga menyoroti pentingnya protes damai dan sarana yang sah untuk mencari perubahan, daripada menggunakan pemberontakan dan kekerasan.Secara keseluruhan, Hadist menekankan pentingnya menjunjung hukum dan menghindari pemberontakan, yang dapat menyebabkan kekacauan dan ketidakstabilan. Umat Muslim diimbau untuk mempertahankan persatuan dan bekerja menuju sarana damai dalam menyelesaikan masalah dan membawa perubahan positif dalam masyarakat. Tulisan ini menyimpulkan bahwa ketaatan pada Hadist dapat menjadi alat yang kuat dalam mempromosikan perdamaian, keadilan, dan harmoni dalam masyarakat.